HUBUNGAN KONSUMSI SUPLEMEN DAN FREKUENSI PEMERIKSAAN KEHAMILAN DENGAN KOMPLIKASI KEHAMILAN - Imaculata Tinneke Tandiono; Triska Susila Nindya; Sri Sumarmi (Media Gizi Indonesia, 2015)
Complication of pregnancy can be induced by anemia in pregnancy which can be caused by deficiency of micronutrients, especially iron, folic acid, minerals and other vitamins. Complication of pregnancy can be prevented by doing routine antenatal care because pregnant women got a supplement to prevent anemia. This study was conducted to analyze the association of the type of supplement and the frequency of antenatal care to complication of pregnancy in Probolinggo district. This was a case control study. Sample taken was 57 people consist of 19 pregnant women who had complication of pregnancy and 38 pregnant women who did not have complication of pregnancy. Three types of supplements that consumed by pregnant women who had complication of pregnancy and pregnant women who did not have complication of pregnancy were in balance proportion (MMN=33,3%, IFA=31,6% and TTD=35,1%). Pregnant women who had complication of pregnancy were doing less than four visits of antenatal care. Types of supplement did not show significant association to complication of pregnancy (p=0,713, while frequency of antenatal care had significant association to complication of pregnancy (p=0,001). Pregnant women should do routine antenatal care to prevent complication of pregnancy.Keywords: complication of pregnancy, frequency of antenatal car, type of supplement